O ensino de geografia na educação quilombola: experiência na Escola Municipal de Ensino Fundamental Professora Antônia Socorro da Silva Machado - Comunidade Negra Paratibe,PB - Cavalcante, Ygor Yuri de Luna (2013)
This dissertation deals with the contributions of the geography subject for an ethno-racial education at the Municipal School of Basic Education Professor Antonia Socorro da Silva Machado ( EMEFPASSM ) , which serves students of the Elementary School II, coming from the quilombola lands of Paratibe s Black Community ( CNP ) , located in the south region of João Pessoa city . Our goal was to investigate the contributions of a scholar Geography to a quilombola s education through a field research about educational practices that were studied by the geography teacher and her students in the classroom. Geography teaching inserted in a context ethno-cultural and political- ideological present in the school with educators, students , school board and municipal and quilombola community with quilombola leaders , shows itself as one of the elements of the school curriculum, training citizens which allows an understanding of their socio-space living realities . In a pursuit of a better understanding of the studied subject, this research is divided into four chapters , each one of them are addressed different theoretical bases, dialogues and interpretations that have been established or accomplished . In the first chapter was held a discussion about the method and the methodological procedures in order to understand the reality experienced in a qualitative perspective . The second chapter deals with the process of construction of this territorial quilombola community , relating their reality with other quilombola communities from a historical rescue summary of the education for African descent and Quilombolas the political demands of them , and how the Geography subject can contribute to this type of education . The third chapter conducts an investigation into the founder and teacher of this school, emphasizes the relationship of the school curriculum quilombola with Law 10.639/03 and its influences in quilombola territorial identity and the struggle against racism in school , finishing from an analysis on the training of the geography teachers for an quilombola education. The fourth chapter attempts to show the field research conducted by an investigation that , at first becomes descriptive , while in the second phase, an analysis is made of the school practices experienced in the classroom .